2017
DOI: 10.1186/s12872-016-0464-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erythropoietin in patients with acute myocardial infarction: five-year results of the REVIVAL-3 trial

Abstract: BackgroundErythropoietin (EPO) has been suggested to promote cardiac repair after MI. However, the randomized, double-blind, placebo controlled REVIVAL-3 trial showed that short term high dose EPO in timely reperfused myocardium does not improve left ventricular ejection fraction after 6 months. Moreover, the study raised safety concerns due to a trend towards a higher incidence of adverse clinical events as well as a increase in neointima formation after treatment with EPO. The present study therefore aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…However, further studies are required to explore the effect of the magnitude of anemia on mortality risk because therapy aimed at regulating hemoglobin level has failed to demonstrate clinical benefit. 17 Our study showed that increased BMI was associated with lower mortality risk. Although obesity is a well-established risk factor for cardiovascular disease, overweight or obese patients with AMI had lower short-and long-term mortality risk than normal weight patients, a phenomenon known as the "obesity paradox".…”
Section: Discussionmentioning
confidence: 54%
“…However, further studies are required to explore the effect of the magnitude of anemia on mortality risk because therapy aimed at regulating hemoglobin level has failed to demonstrate clinical benefit. 17 Our study showed that increased BMI was associated with lower mortality risk. Although obesity is a well-established risk factor for cardiovascular disease, overweight or obese patients with AMI had lower short-and long-term mortality risk than normal weight patients, a phenomenon known as the "obesity paradox".…”
Section: Discussionmentioning
confidence: 54%
“…Even though both mild and moderate to severe anemia did predict an increased risk for long-term mortality independent of a number of confounders in our study population, treatment strategies that aim at increasing Hb concentration in patients with AMI and anemia might not significantly benefit long-term survival. In line, a recent randomized controlled trial demonstrated that administering erythropoietin after PCI, a hypoxia-induced hormone that also regulates Hb concentration, did not have beneficial effects on long-term outcomes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although consistent results in small rodents indicated erythropoietin as useful in reducing the myocardial infarction area and promoting cardiac repair (156), human studies didn't confirm these effects. The issue seems to be the timing of erythropoietin administration (157) and also with the adverse events.…”
Section: Erythropoietinmentioning
confidence: 99%